Evaluation of urgent and emergency care in a primary care unit in a small municipality in the interior of Vale of Taquari (Research, Society and Development, 2020)
The number of urgencies and emergencies recorded daily across the country is relevant. Many of the occurrences attended in primary care itself occur due to the lack of hospitals in small municipalities, having Primary Health Care as their first and only choice. Professionals need to be trained and able to perform the risk classification and attend to these serious cases. The objective of the study was to know, investigate the patients' cases, analyze the perceptions of the professional team, verifying the difficulties encountered, and, thus, propose improvements in the provision of services. The methodology used was qualitative and an interview with the team was applied. With the results, it was possible to analyze the types of care provided at the chosen unit, such as the triage / reception of urgent and emergency cases, the risk classification, the average time / referral of the patient attended and the use of the golden hour, as well as the procedures used in the visits and the difficulties and perceptions encountered by the team. It was concluded that there is difficulty on the part of the professionals in the assistance, due to the lack of preparation through continuing education and lack of equipment and structure.